2014
DOI: 10.2341/13-294
|View full text |Cite
|
Sign up to set email alerts
|

10-year Follow-up of Natural Crown Bonding After Tooth Fracture

Abstract: SUMMARY The aim of this article is to discuss relevant considerations about crown bonding and describe a clinical case in which a tooth fragment and direct composite resin were used to successfully restore a fractured anterior tooth. Clinical examinations showed good esthetics and periodontal health after 10 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…Despite the fracture simulation with a diamond cutting disk not being fully compatible with clinical situations, it was the standard methodology used in previous studies evaluating fracture resistance after fragment bonding . The compressive force exerted on the fragment was the same (1 mm/min −1 ) for all the specimens and occurred at 2.5 mm from the incisal edge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fracture simulation with a diamond cutting disk not being fully compatible with clinical situations, it was the standard methodology used in previous studies evaluating fracture resistance after fragment bonding . The compressive force exerted on the fragment was the same (1 mm/min −1 ) for all the specimens and occurred at 2.5 mm from the incisal edge.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fracture simulation with a diamond cutting disk not being fully compatible with clinical situations, it was the standard methodology used in previous studies evaluating fracture resistance after fragment bonding. 3,6,10,18,[31][32][33]35,36 The compressive force exerted on the fragment was the same (1 mm/min −1 ) for all the specimens and be explained by the action of water and its ability to establish polar bonds through hydrogen bridges with the peptides from collagen fibrils, causing a rapid re-expansion of fibrils that had collapsed due to dehydration and allowing the formation of an optimized hybrid layer. 27,37,38 The study conducted by Capp et al 31 showed that 30 minutes of fragment rehydration following dehydration for 48 hours led to a higher fracture resistance compared with 48 hours dehydration alone.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, apenas uma pequena quantidade de material restaurador fica exposta na superfície vestibular. Por conseguinte, essa técnica tem demonstrado altas taxas de sucesso (6,21,23,(32)(33)(34). O procedimento clínico é seguro, minimamente invasivo, simples, rápido, menos oneroso e proporciona ao paciente condições emocionais e sociais altamente positivas (6,21,31,32,35,36).…”
Section: Tratamento Restauradorunclassified
“…Apesar de todas as vantagens supracitadas, a técnica executada na colagem de fragmento apresenta muitas variações, sejam elas: a existência de preparo adicional com broca, o sistema adesivo utilizado (1, 2 ou 3 passos; autocondicionantes ou com condicionamento prévio) ou, ainda, o material intermediário (resina composta, resina "flow", cimento resinoso ou ionômero de vidro) escolhido. Além disso, cerca de 50% das colagens de fragmento se soltam em até 2,5 anos e, na maioria dos casos, a falha ocorre devido a novos traumas ou à função não fisiológica do dente, corroborando para que a essa técnica continue a ser investigada (23,34), embora haja casos clínicos que relatem um acompanhamento de anos e resultados satisfatórios (4,39).…”
Section: Tratamento Restauradorunclassified
See 1 more Smart Citation